Statistical optimisation of diesel biodegradation at low temperatures by an Antarctic marine bacterial consortium Isolated from non-contaminated seawater - Zakaria, Nur Nadhirah; Gomez-Fuentes, Claudio; Abdul Khalil, Khalilah; Convey, Peter; Ahmad Roslee, Ahmad Fareez; Zulkharnain, Azham; Sabri, Suriana; Shaharuddin, Noor Azmi; Cardenas, Leyla; Ahmad, Siti Aqlima (MDPI AG, 2021)
Hydrocarbon pollution is widespread around the globe and, even in the remoteness of Antarctica, the impacts of hydrocarbons from anthropogenic sources are still apparent. Antarctica’s chronically cold temperatures and other extreme environmental conditions reduce the rates of biological processes, including the biodegradation of pollutants. However, the native Antarctic microbial diversity provides a reservoir of cold-adapted microorganisms, some of which have the potential for biodegradation. This study evaluated the diesel hydrocarbon-degrading ability of a psychrotolerant marine bacterial consortium obtained from the coast of the north-west Antarctic Peninsula. The consortium’s growth conditions were optimised using one-factor-at-a-time (OFAT) and statistical response surface methodology (RSM), which identified optimal growth conditions of pH 8.0, 10 °C, 25 ppt NaCl and 1.5 g/L NH4NO3. The predicted model was highly significant and confirmed that the parameters’ salinity, temperature, nitrogen concentration and initial diesel concentration significantly influenced diesel biodegradation. Using the optimised values generated by RSM, a mass reduction of 12.23 mg/mL from the initial 30.518 mg/mL (4% (w/v)) concentration of diesel was achieved within a 6 d incubation period. This study provides further evidence for the presence of native hydrocarbon-degrading bacteria in non-contaminated Antarctic seawater.